Pembuatan Media Pembelajaran Interaktif Menggunakan Unity Berbasis Andorid pada Mata Pelajaran Informatika - Adif, Anjjani Mardhika; Wijaya, Indra; Sefriani, Rini (Journal of Research and Investigation in Education, 2025)
This study aims to analyze the validity, practicality and effectiveness of Interactive Learning Media Using Unity Based on Android in Informatics Subjects for Class X at SMKN 9 Padang. This study uses a research and development (R&D) method, using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 35 students of class X majoring in Culinary 4. The results of the study showed that the overall validity test by experts on interactive learning media based on Android using Unity for class X at SMK Negeri 9 Padang was 91.03%, so the level of validity can be interpreted as very valid to use. The overall practicality test assessment of interactive learning media based on Android using Unity for class X at SMK Negeri 9 Padang was 89.44%, so the level of practicality can be interpreted as very practical to use. The overall effectiveness test assessment of android-based interactive learning media using Unity for class X at SMK Negeri 9 Padang was 88.12%, so the level of effectiveness can be interpreted as very effective to use. The conclusion of this study is to produce an interesting and useful android-based interactive learning media application for teachers and students both during face-to-face or online learning.